2004
DOI: 10.1051/lait:2004010
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence and infrared spectroscopies: a tool for the determination of the geographic origin of Emmental cheeses manufactured during summer

Abstract: -Mid-infrared (MIR) and front-face fluorescence spectroscopies, coupled with chemometric techniques, were investigated for their potential for discriminating Emmental cheeses originating from various geographic origins. A total of 74 Emmental cheeses, produced during summer, from six countries, i.e., Denmark (n = 2), Finland (n = 4), Germany (n = 6), Austria (n = 8), France (n = 27) and Switzerland (n = 27) were analysed. Within the 1500-900 cm -1 spectral region, a good classification of samples was obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 20 publications
7
22
0
Order By: Relevance
“…These results, which were not obtained by FDA performed on each of the tryptophan, AAA+NA, vitamin A or riboflavin fluorescence spectral data sets, showed that the concatenation methodology allowed the use of all the spectroscopic information given by the four intrinsic probes in a very efficient way. The current study is in agreement with previously published data, indicating that fluorescence spectra can be used for the determination of the geographic origin of Gruyère PDO and L'Etivaz PDO cheeses [15] and of European Emmental cheeses [23,24].…”
Section: Global Analysis Of the Fluorescence Spectral Data Recorded Osupporting
confidence: 92%
See 1 more Smart Citation
“…These results, which were not obtained by FDA performed on each of the tryptophan, AAA+NA, vitamin A or riboflavin fluorescence spectral data sets, showed that the concatenation methodology allowed the use of all the spectroscopic information given by the four intrinsic probes in a very efficient way. The current study is in agreement with previously published data, indicating that fluorescence spectra can be used for the determination of the geographic origin of Gruyère PDO and L'Etivaz PDO cheeses [15] and of European Emmental cheeses [23,24].…”
Section: Global Analysis Of the Fluorescence Spectral Data Recorded Osupporting
confidence: 92%
“…Indeed, Wold et al [41] have demonstrated that fluorescence properties of riboflavin can be used to measure the degree of degradation of riboflavin in dairy products. Finally, it has been shown that front-face spectroscopy allows the determination of the geographic origin of Gruyère and L'Etivaz PDO cheeses [15,24] and of Emmental cheeses from different European geographic origins [23,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 2b, there was a good discrimination between farmhouse cheeses and the others, which was not observed for cheese samples obtained by using the laboratory spectrofluorometer. The obtained results partially confirmed the findings of Karoui et al [9,13], reporting that a maximum located around 345 nm was observed for different cheese varieties and was attributed to tryptophan residues. The difference observed between the shapes of the spectra recorded on the investigated cheese samples could be due to the different molecular environments of tryptophan residues.…”
Section: Fluorescence Spectra Of Different Cheese Samplessupporting
confidence: 90%
“…The absorption bands observed in the MIR range of 4000-600 cm -1 are associated with fundamental valence vibrations of functional groups of the molecule. For a given cheese, a good repeatability is obtained from the three spectral measurements [19,20].…”
Section: Resultsmentioning
confidence: 95%